Idiopathic recurrent pericarditis — a paradigm shift? - V. Yu. Myachikova; V. A. Titov; A. L. Maslyanskiy; O. M. Moiseeva (Российский кардиологический журнал, 2019)
Idiopathic recurrent  pericarditis (IRP) is a relatively rare inflammatory disease of the pericardium,  often  requiring  emergency medical  care,   associated with a  high percentage of temporary  disability and  significant  economic  costs.  The review presents various  points  of view on  the  pathogenesis of recurrent   pericarditis, discusses the role of autoinflammation.  It touches on treatment issues  based  on modern  data  on the IRP immunopathogenesis, and considers promising areas  of laboratory diagnostics.